Development of a Stepwise Expanding Pitch Fruit Grader - Mangaraj, S; Varshney, A C; Reddy, B S; Singh, K K (Journal of Agricultural Engineering, 2005)
In view of the importance of grading of fruits, a stepwise expanding pitch fruit grader based on the principle of changing the flap spacing along the length of movement of fruits was developed. The main components of the fruit grader are grading unit, elevator feeding unit, inspection platform and power transmission system. The grading unit consisted of two tracks of conveyor chains, matching sprockets, stainless steel flaps, conveyor supporters, flap space adjusting mechanism, power source, power transmission system and fruit collection trays. The elevator feeding unit is provided for constant and uniform feeding of fruits into the grading unit. The Inspection plat form is provided for removal of damaged, diseased and unwanted fruits before they are fed to the elevator feeding unit. Cushioning material has been glued to the inspection platform, fruit collection tray and flaps to avoid impact damage at the time of grading. The grader has the provision to separate fruits into four grades by adjusting flap spacing between 45 to 140 mm. Testing of the fruit grader showed overall grading efficiency of 91.50% and 88.50%.for sweet lemon and orange, respectively. The capacity of the grader was 3.5 t/h at grading conveyor speed of 6 m/min. and there wasno damage to the fruits while grading.